Personal and environmental determinants of consumer legal literacy among Malaysian consumers - Samsudin, Norhafifah; Abu Bakar, Elistina; Md Jusoh, Zuroni; Muhammad Arif, Afida Mastura (Malaysia Consumer And Family Economy Association (MACFEA), 2020)
Legal literacy means whether the consumers have the knowledge and are able to apply the information when they make transactions, and thus more likely know how to seek redress. The objective of this article is to analyze the determining factors of consumer legal literacy among Malaysian consumers. A survey was conducted among 500 respondents who were chosen through systematic random sampling. Standard multiple linear regressions results show that only value, self-efficacy, and peer influence can explain thirteen point four percent (13.4%) variance and the most influencing factor was peer influence. This research holds significant implications for the government, educators, and consumer movements to emphasize effective consumer education programs to increase literacy among consumers. It is also necessary to establish more comprehensive programs, either through formal or informal education, especially in instilling good values among consumers. Self-efficacy and peer influence can be considered in consumer education programs such as those by the Ministry of Domestic Trade and Consumer Affairs, consumer movements, and consumer clubs in schools.